The Post 1997-Crisis Democratization In South Korea: A Case Study of Industrial Relations - Tulus Warsito (Universitas Muhammadiyah Yogyakarta, 2013)
The field research was set to find out the correlations between the 1997 monetary crisis and the process of democratic consolidation in South Korea, especially in term of industrial relations. As complementary components of industrialization; state, business and labors are, by nature, often performed conflicting actions. Like in many other developing countries or newly industrializing countries, South Korea experienced a strong developmental state regime where state has a very tight relation with business group, while their labor policy was badly repressive. But as the 1997 crisis occurred, the three conflicting and competing parties seemed to agree to some points according to solve the problems affected by the crisis. The process of democratic consolidation seems to be swifted because of it. The question of why the crisis seems to swift the democratization needs to be observed by then. The research was started by exploring the cause and impact of the crisis to the three parties. Some facts were found that the 1997 crisis affected all the economic, social and political sectors of the nation, which by any means it became a common threat of the nation. Some strategic recovery programs were set up, some agreement were signed up, and by then the democratic consolidation were being confirmed.